Learning Informatica PowerCenter 10.x : enterprise data warehousing and intelligent data centers - Malewar, Rahul (Packt Publishing, 2017)
Harness the power and simplicity of Informatica PowerCenter 10.x to build and manage efficient data management solutions About This Book Master PowerCenter 10.x components to create, execute, monitor, and schedule ETL processes with a practical approach. An ideal guide to building the necessary skills and competencies to become an expert Informatica PowerCenter developer. A comprehensive guide to fetching/transforming and loading huge volumes of data in a very effective way, with reduced resource consumption Who This Book Is For If you wish to deploy Informatica in enterprise environments and build a career in data warehousing, then this book is for you. Whether you are a software developer/analytic professional and are new to Informatica or an experienced user, you will learn all the features of Informatica 10.x. A basic knowledge of programming and data warehouse concepts is essential. What You Will Learn Install or upgrade the components of the Informatica PowerCenter tool Work on various aspects of administrative skills and on the various developer Informatica PowerCenter screens such as Designer, Workflow Manager, Workflow Monitor, and Repository Manager. Get practical hands-on experience of various sections of Informatica PowerCenter, such as navigator, toolbar, workspace, control panel, and so on Leverage basic and advanced utilities, such as the debugger, target load plan, and incremental aggregation to process data Implement data warehousing concepts such as schemas and SCDs using Informatica Migrate various components, such as sources and targets, to another region using the Designer and Repository Manager screens Enhance code performance using tips such as pushdown optimization and partitioning In Detail Informatica PowerCenter is an industry-leading ETL tool, known for its accelerated data extraction, transformation, and data management strategies. This book will be your quick guide to exploring Informatica PowerCenter's powerful features such as working on sources, targets, transformations, performance optimization, scheduling, deploying for processing, and managing your data at speed. First, you'll learn how to install and configure tools. You will learn to implement various data warehouse and ETL concepts, and use PowerCenter 10.x components to build mappings, tasks, workflows, and so on. You will come across features such as transformations, SCD, XML processing, partitioning, constraint-based loading, Incremental aggregation, a ...